1977
DOI: 10.1007/bf00606409
|View full text |Cite
|
Sign up to set email alerts
|

Agranulocytosis during treatment with clozapine

Abstract: Within six months of the introduction of the new antipsychotic drug clozapine in Finalnd, 17 cases of neutropenia or agranulocytosis were recorded amongst about 3000 patients treated. Agranulocytosis was fatal in eight patients, and in addition, two patients developed thrombocytopenia, and one patient leukaemia. As additional cases might well have been overlooked as banal infections, the risk of developing agranulocytosis during clozapine treatment was at least 0.5%. Impaired elimination of the drug or increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
2

Year Published

1990
1990
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(58 citation statements)
references
References 5 publications
1
55
0
2
Order By: Relevance
“…The risk of agranulocytosis associated with ticlopidine 14 and clozapine 17,18 had already been uncovered in clinical trials.…”
Section: Commentmentioning
confidence: 99%
“…The risk of agranulocytosis associated with ticlopidine 14 and clozapine 17,18 had already been uncovered in clinical trials.…”
Section: Commentmentioning
confidence: 99%
“…Despite its tendency to induce agranulocytosis (Idanpaan-Heikkila et al 1977), the atypical neuroteptic clozapine is an effective psychotherapeutic agent in treatment-resistant schizophrenic patients (e.g., Meltzer 1992a); moreover, clozapine has a quite low incidence of inducing extrapyramidat side effects (Schmauss et al 1989;Meltzer 1992b). The therapeutic success of this drug has spurred the search for clozapine-like drugs without leukocytopenic side effects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the well documented evidence associating neurological abnormalities with schizophrenia, there is some evidence that hematologic disturbances may be associated with genetic vulnerability to schizophrenia. Studies have shown that risk for clozapine-induced agranulocytosis may vary by ethnicity with rates for Finnish (12) and Jewish (13) populations being particularly elevated. Other investigators studying subjects from the Copenhagen schizophrenia high-risk project have hypothesized that disturbances in fetal neuronal development that are under genetic control may be associated with an increased vascular sensitivity to periventricular hemorrhage (14).…”
Section: Introductionmentioning
confidence: 99%